Sistematic Literature Review Dampak Penggunaan Gadget Pada Konsentrasi Dan Minat Belajar Di Sekolah Dasar - Rika Tamala; Rusmala Dewi; Wahyullah Alannasir; Chelsy Ayunda Sari; Siti Ayudiah Alim; Ibnu Sina; Irfan (Jurnal Lazuardi, 2026)
This study aims to examine the influence of gadget use on elementary school children's concentration levels and learning interest through a qualitative strategy based on a Systematic Literature Review (SLR). This analysis combines principles of Educational Technology, Educational Psychology, and Developmental Psychology to explore the relationship between digital technology and early childhood learning patterns. Data is sourced from 10 scientific publications from 2020–2026, processed through a gradual process of searching, filtering, critical appraisal, and reorganization. Key findings reveal the dual nature of gadgets' impact: beneficial aspects are seen when these devices are used as interactive teaching aids, capable of stimulating students' motivation, interest, and conceptual mastery. However, detrimental effects arise when uncontrolled use occurs, such as reduced focus, increased distraction, and children's preference for entertainment over schoolwork. Furthermore, excessive use can potentially hinder children's cognitive development and social interaction. Therefore, parents and educators need to play a proactive role in guiding and limiting gadget use to align with educational goals. This study is expected to provide a foundation for developing an intelligent and balanced learning approach at the elementary school level.